Associations of household dampness and cold exposure with cardiovascular disease and symptoms among elderly people in Chongqing and Beijing. (1st April 2023) - Guo, Miao; Yu, Wei; Zhang, Yan; Li, Baizhan; Zhou, Haixia; Du, Chenqiu
Abstract: Atmospheric temperature and humidity are associated with cardiovascular disease mortality and morbidity, with elderly people spending more than 80% of their time indoors. Indoor temperature and humidity may have a greater impact on the elderly's health. A cross-sectional study among adults over 60 years of age in Beijing (n = 833) and Chongqing (n = 858) was conducted to investigate household dampness exposure and cold exposure in their residences and the prevalence of hypertension and cardiovascular symptoms (palpitation, premature beat, tachycardia, angina pectoris, chest distress, chest pain, dizziness, and headache). Associations and number–response relationships between dampness and cold exposures and cardiovascular symptoms were calculated using multifactorial logistic regression models. The results showed that the proportion of residences with dampness and cold exposure was significantly higher in Chongqing than in Beijing. Household dampness exposure is associated with increased hypertension and eight cardiovascular symptoms, whereas cold exposure is associated with an increase in eight cardiovascular symptoms. In the stratified analysis, the number of cardiovascular symptoms associated with household dampness exposure in the Chongqing study was higher than that in the Beijing study, whereas the number of cardiovascular symptoms associated with cold exposure in the Beijing study was higher than that in the Chongqing study. In most cases, the five household dampness indicators generally had stronger associations with eight cardiovascular symptoms in Chongqing than in Beijing. There were significant number–response relationships between the cumulative scores of dampness indicators in the elderly residents and the increased prevalence of cardiovascular symptoms in the Chongqing study. Highlights: The proportions of household dampness and cold exposure were higher in Chongqing (wet region) than in Beijing (cold region). Household dampness and cold exposures were associated with cardiovascular symptoms. The associations between the dampness indicator and cardiovascular symptoms were stronger in Chongqing than in Beijing. The associations between cold exposure and cardiovascular symptoms were stronger in Beijing than in Chongqing. Cumulative scores of dampness indicators had number–response relationships with cardiovascular symptoms.